A Note on the Flare Stars in the Coalsack - B. Hidajat; A. Kuncoro (Journal of Mathematical and Fundamental Sciences, 1974)
Ringkasan. Didalam tulisan ini dilaporkan penemuan 5 buah "flare stars" di daerah Coalsack.  Abstract. The discovery of 5 flare stars in the Coalsack is reported.